2009
DOI: 10.1016/j.apcata.2009.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic performance enhancement by heat treatment of CuFe2O4 spinel and γ-alumina composite catalysts for steam reforming of dimethyl ether

Abstract: The influence of heat treatment on catalytic activity and durability for steam reforming of dimethyl ether (DME SR) over the composite catalysts of CuFe 2 O 4 spinel and γ-Al 2 O 3 was investigated. The heat treatment in air after mixing of CuFe 2 O 4 and Al 2 O 3 improved the activity and durability of the composite catalysts for DME SR. The treatment temperature range of 700-800 o C is the most effective to enhance the catalytic performance. According to XRD and TPR analyses, the new phase of Cu-Fe-AlO 4 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…On the other hand, the similar variations are also found for the pore volume and pore diameter, which indicates that the pore structure of the catalysts are affected by the pronounced increase in particle sizes [32]. Nevertheless, these catalysts show much higher surface area than those spinels obtained from sol-gel methods [33,34]. Furthermore, the BET surface area of CCA-IM (112 m 2 /g) decreases compared to that of Al 2 O 3 (250 m 2 /g), which is due to the pore blockage by the metal oxides particles.…”
Section: Textural Propertiessupporting
confidence: 68%
“…On the other hand, the similar variations are also found for the pore volume and pore diameter, which indicates that the pore structure of the catalysts are affected by the pronounced increase in particle sizes [32]. Nevertheless, these catalysts show much higher surface area than those spinels obtained from sol-gel methods [33,34]. Furthermore, the BET surface area of CCA-IM (112 m 2 /g) decreases compared to that of Al 2 O 3 (250 m 2 /g), which is due to the pore blockage by the metal oxides particles.…”
Section: Textural Propertiessupporting
confidence: 68%
“…Various thermal treatment conditions were systematically investigated to originate their roles on treated catalysts [4,43]. Figure 9 demonstrates the effect of calcination temperature of the composite catalyst of CuFe 2 O 4 and Al 2 O 3 (ALO8) on DME conversion in DME SR (replotted from [4]).…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…Research and development of the composite catalysts have attracted much attention as one of the key technologies in applying them to fuel cell system commercially. This article reviews and introduces recent progress of development of DME SR catalysts mainly done by our research group, including roles of solid-acid catalysts [24,30], copper spinel structures [29,31,41,43,44], preparation method [3,4,29,38], and reaction conditions [24, 29-31, 33, 38, 41, 43-45] as well as catalytic behaviors, deactivation, and regeneration of the catalysts [3,47].…”
Section: Introductionmentioning
confidence: 99%
“…One novel approach to disperse metal nanoparticles on oxide supports has been proposed as crystalline phase separation of parent complex oxides during reduction process (Faungnawakij et al 2009, Shimoda et al 2010. It has been demonstrated that Cu nanoparticles can be formed on the iron oxide (Fe 3 O 4 ) host from original copper-iron spinel oxide (CuFe 2 O 4 ).…”
Section: Metal and Metal Oxide Nanoparticlesmentioning
confidence: 99%